AVALIAÇÃO DA CITOTOXICIDADE, CITOPROTEÇÃO E EFEITOS DOS FLAVONÓIDES RUTINA E HESPERIDINA SOBRE A FUNCIONALIDADE DE CÉLULAS SECRETORAS DE INSULINA BRIN-BD11 - Felipe, Elise Tatiane (2011)
Diabetes mellitus is now a major public health problems, with increasing numbers of incidence, and has been considered an epidemic. Several studies demonstrate the relationship between diabetes mellitus and oxidative stress. Thus bioactive compounds with potential to act by preventing or mitigating the consequences of this process are interesting. In this category are the flavonoids, compounds with antioxidant activity is well established, marked by its reactive species scavenger capacity and thereby have the potential to act in the treatment or prevention of diabetes. Therefore, the objective was to evaluate the in vitro effects in the cytotoxic, cytoprotective and functionality of insulin-secreting cells BRIN-BD11 of the flavonoids rutin and hesperidin. The methods were used: MTT reduction method (assessment of cell viability), radioimmunoassay (assessment of insulin secretion), and the enzymatic rate method for determining the maximum activity of glutathione peroxidase (GSH-Px). The experiment of cytotoxicity was not observed cytotoxic effect of the flavonoids rutin and hesperidin in all tested concentrations (1.25, 2.5, 5, 10, 20, 40 and 80 μM) after 24 hours of treatment. The flavonoids rutin and hesperidin concentrations of 2.5, 5 and 10 μM showed no cytoprotective effects on BRIN-BD11 cells under oxidative stress induced by exposure to hydrogen peroxide (37.5 μM-sub-lethal and lethal-75 μM ). In this test the flavonoids and hydrogen peroxide were added simultaneously and remained in contact with the cells for 24 hours. BRIN-BD11 cells were pretreated (24 hours) with rutin and hesperidin (10 μM) and subsequently subject to oxidative stress induced by hydrogen peroxide (350 μM) for 2 hours. In this condition also was not observed cytoprotective effect of flavonoids. Rutin and hesperidin (1.25, 2.5, 5, 10, 20, 40 and 80 μM) had no insulinotropic BRIN-BD11 cells after 24 hours of treatment. After treatment BRIN-BD11 cells for 24 hours in the presence of the flavonoids rutin and hesperidin (10 μM) was not observed change in the activity of glutathione peroxidase (GSH-Px). Thus, it is concluded that the flavonoids rutin and hesperidin are safe, showing no cytotoxicity on BRIN-BD11 cells, but showed no cytoprotective effects and insulinotropic on the conditions tested.